The Representation of Social Actors in First 100 Days of Office of Jokowi-Basuki - Fira Nursya'bani (Passage, 2014)
This journal presents the analysis of how the national mass media deliver their ideological point of view to the readers in their online articles regading a political issue in Joko Widodo and Basuki Tjahja Purnama first 100 days of office. It was aimed at investigating the way social actors are represented in the text and to uncover the ideologies underlying the representation. The data were obtained from ten online articles from different nationwide media published in 22 January 2013. A qualitative method was employed to analyse the selected data. The data were analysed based on the sociosemantic approach proposed by Van Leeuwen (2008). The findings showed that Jokowi as the governor of Jakarta was dominated the occurrences as an active participant. Moreover, different impression was shown where the active roles were always associated with Jokowi and the passive roles were always associated with Jakarta. The findings also revealed that the possible ideologies that can be inferred from the representation were democracy and Jokowi as the “city rescuer.”Keywords: Critical Discourse Analysis, Social Actors, Van Leeuwen’s Sociosemantic, Inclusion/Exclusion, Jokowi, Basuki, Jakarta